Interventions Targeting the Wellbeing of Migrant Youths: A Systematic Review of the Literature. (September 2021) - Heyeres, Marion; Perera, Nirukshi; Udah, Hyacinth; Attakey, Akpene; Whiteside, Mary; Tsey, Komla
Migration can affect the physical, mental, emotional, and social wellbeing of individuals and families. This study provides an overview of interventions aimed at improving the wellbeing of young migrants. It identifies knowledge gaps and provides direction for future research. The review process comprises a systematic search of six academic databases, and websites for relevant peer-reviewed and gray literature on the topic. A total of 2, 911 records were identified, of which 28 studies met our eligibility criteria for inclusion. Thematic analysis comprised of the description of study characteristics and outcome themes. EPHPP and CASP tools were utilized to assess the methodological quality of studies. The review findings indicate a number of approaches with varying effectivity, however, arts, music, and sports programs showed good results for youth across all migrant groups. Our findings call for further and more high-quality evaluation research, with longitudinal designs that ideally include stakeholder collaboration.